2020
DOI: 10.1038/s41598-020-67297-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of Trichinella papuae muscle-stage larvae

Abstract: Outbreaks of trichinellosis caused by Trichinella papuae have been reported in SouthEast Asia. Mebendazole and thiabendazole are the treatments of choice for trichinellosis; however, both drugs result in significant side effects and are less effective for muscle-stage larvae (L1). An alternative therapeutic agent is needed to improve treatment. Information on lipid composition and metabolic pathways may bridge gaps in our knowledge and lead to new antiparasitics. The T. papuae L1 lipidome was analysed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…Glycerophospholipids and glycerolipids were the major lipid groups in all three sample groups (NB_SE, NB_ESP, and TM_SE), constituting approximately 83% of the total lipids. This is in congruence with lipidomic studies in the muscle-stage larvae of Trichinella papuae (~63% glycerophospholipids) [123] and in the H. contortus (all life-cycle stages), where more than 90% of the total lipids were glycerophospholipids and glycerolipids [119]. The somatic extract of N. brasiliensis L3 contained elements of glycerophospholipids such as phosphatidylcholine, PC (38:6), PC(40:8), PC(40:7), PC(40:9), and PC (46:5).…”
Section: Discussionsupporting
confidence: 86%
“…Glycerophospholipids and glycerolipids were the major lipid groups in all three sample groups (NB_SE, NB_ESP, and TM_SE), constituting approximately 83% of the total lipids. This is in congruence with lipidomic studies in the muscle-stage larvae of Trichinella papuae (~63% glycerophospholipids) [123] and in the H. contortus (all life-cycle stages), where more than 90% of the total lipids were glycerophospholipids and glycerolipids [119]. The somatic extract of N. brasiliensis L3 contained elements of glycerophospholipids such as phosphatidylcholine, PC (38:6), PC(40:8), PC(40:7), PC(40:9), and PC (46:5).…”
Section: Discussionsupporting
confidence: 86%
“…Their abundance in these samples is likely associated with them being common building blocks of membrane bilayers [42]. Similar to previous studies of parasitic nematodes [26][27][28], we showed that the amounts of PC were significantly higher than PE in the lipidome of A. suum. In addition, the https://doi.org/10.1371/journal.pntd.0008848.g007…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
“…Recently, advanced atmospheric pressure scanning microprobe matrix-assisted laser desorption/ionisation (AP-S-MALDI) mass spectrometry imaging (MSI) was used, for the first time, to characterise the lipid composition of S. mansoni tissues in a spatially-resolved manner [25]. However, a paucity of lipidomic work has been conducted on parasitic nematodes, with most studies focused predominantly on specific lipid categories or a single life-cycle stage [26,27]. Recently, we characterised the lipidome of Haemonchus contortus (barber's pole worm of ruminants) for six key developmental stages/sexes [28] and subsequently explored the lipidome of specific organs of the adult female of this species [29].…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain fatty acid transport protein 1 is also found in T . papuae [ 50 ] and may be a useful early diagnostic marker of T . spiralis .…”
Section: Discussionmentioning
confidence: 99%